HUBUNGAN ANTARA DURASI PENGGUNAAN JEJARING SOSIAL DAN TINGKAT FEAR OF MISSING OUT DI KALANGAN MAHASISWA KEDOKTERAN DI JAKARTA - Felix Setiadi; Dharmady Agus (Bahasa Indonesia, 2020)
Introduction: Fear of Missing Out (FoMO) is a type of anxiety disorder when someone feels afraid that they will be left out of new experiences that were experienced by others. This is marked by the desire to stay connected with what other people are doing. One of the causes of FoMO is the increasing usage of social networks. The social network has been used in daily life and has been globalized. FoMO was more prevalent in adolescents and young adults because they were more adaptable to new technology and lack self-regulation. This study aims to determine the relationship between FoMO level and social network usage duration among medical students in Atma Jaya Catholic University of Indonesia. Methods: The study is an analytical study with a cross-sectional approach, with a total of 150 respondents. The respondents consisted of the class year 2016, 2017, and 2018 medical students at Atma Jaya Catholic University of Indonesia and selected by random cluster sampling. The data were collected by distributing the Fear of Missing Out scale (FoMOs) questionnaire to measure fear of missing out level and SONTUS to measure social network usage duration. Data analysis was done with the computer program. Results: The majority of subjects were female (n=99), the respondents aged around 18-21 years. The respondents with a high level of FoMO were 35 respondents. From this high level of FoMO group, most respondents were female (n=21) and spent more time on social networks (n=23). There is a significant correlation between FoMO level and social network usage (p=0,034). Conclusion: There is a significant correlation between Fear of Missing Out level and duration of social network usage.